Elastomeric Indoor Organic Photovoltaics with Superb Photothermal Endurance (Adv. Funct. Mater. 30/2022). (25th July 2022) - Kim, Tae Hyuk; Lee, Ho Jin; Saeed, Muhammad Ahsan; Son, Jae Hoon; Woo, Han Young; Kim, Tae Geun; Shim, Jae Won
Abstract : Elastomeric Indoor Organic Photovoltaics In article number 2201921, Tae Geun Kim, Jae Won Shim, and co‐workers unveil critical factors pertinent to the performance degradation of the indoor organic photovoltaics under indoor photothermal and mechanical stresses. Morphological evolution and molecular packing variation of the photoactive layers with varying photoactive components under indoor stimuli are deeply investigated.